Common arterial trunk with interruption of the aortic arch; a rare association of complex anomalies. Case report - Solano Montero, Armicson Felipe; Aguirre Martínez, María Alejandra; Hurtado, David; Madrid Pinilla, Antonio José (Prenatal Cardiology, 2024)
The common arterial trunk is involved in 1-4% of major congenital heart diseases. It consists of a single arterial trunk that leaves the heart through a single arterial valve, giving rise to the coronary arteries, aorta, and one or two pulmonary arteries. It has an incidence of between 9 and 11 per 100,000 births, and in 35-45% it is associated with microdeletion 22q11.2. It occurs with greater severity in cases with interruption of the aortic arch, with a mortality rate of up to 76% without intervention. The aim of the article is to present the case of a patient with a prenatal diagnosis of the common arterial trunk, associated with type B interruption of the aortic arch, emphasising the importance of the correct classification of this pathology, to define procedures after birth and thus determine its prognosis. The case was a 21-year-old patient, with an ultrasound of fetal anatomical detail showing a perimembranous defect in the interventricular septum, altered aorto-pulmonary relationship, and left outflow tract which reached the supra-aortic trunks without continuity towards the descending aorta. The fetal echocardiogram reported common arterial trunk with interruption of the aortic arch, type A4 in the Van Praagh classification. No genetic study was performed due to the patient’s lack of authorisation. At birth, she underwent surgical correction with progressive deterioration until death. Common arterial trunk with interruption of the aortic arch is a rare pathology with a high mortality rate without surgical intervention, being a diagnostic challenge, despite advances in technology.